1991
DOI: 10.2136/sssaj1991.03615995005500050033x
|View full text |Cite
|
Sign up to set email alerts
|

Freezing Effects on Aggregate Stability Affected by Texture, Mineralogy, and Organic Matter

Abstract: Aggregate stability, an important property influencing a soil's response to erosive forces, is affected by freezing. The objectives of this laboratory study were to determine how constrainment, number of freeze-thaw cycles, and water content at freezing affect the aggregate stability of six continental USA soils differing in texture, mineralogy, and organic-matter content. Moist aggregates, after being frozen and thawed either zero, one, three, or five times, were vapor wetted to 0.30 kg kg-' and analyzed by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(137 citation statements)
references
References 22 publications
6
128
1
1
Order By: Relevance
“…Four or five days following the third irrigation, except for the first replication of Test 1, we took 5-mmdeep surface soil samples from four locations in each box for wet aggregate stability determinations. The soil samples were lifted from the soil surface with spatulas, sealed in plastic bags, and refrigerated prior to analysis according to the procedure described by Kemper and Rosenau (1986) as modified by Lehrsch et al (1991). After collecting aggregate stability samples, we removed about 40 mm of surface soil from all boxes to ensure that no residual PAM remained (Malik et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Four or five days following the third irrigation, except for the first replication of Test 1, we took 5-mmdeep surface soil samples from four locations in each box for wet aggregate stability determinations. The soil samples were lifted from the soil surface with spatulas, sealed in plastic bags, and refrigerated prior to analysis according to the procedure described by Kemper and Rosenau (1986) as modified by Lehrsch et al (1991). After collecting aggregate stability samples, we removed about 40 mm of surface soil from all boxes to ensure that no residual PAM remained (Malik et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Sugar beet was planted into a moist seedbed in early spring per standard grower practice. The soil studied in the laboratory and at Field Sites 1 and 3 was a structurally unstable Portneuf silt loam, a coarse silty, mixed, superactive, mesic Durinodic Xeric Haplocalcid (Lehrsch et al, 1991). The Portneuf's Ap horizon contained about 560 g silt kg-I and 220 g clay kg-I (USDA classification).…”
Section: Polymer and Soil Characteristicsmentioning
confidence: 99%
“…The aggregate stability of these samples was measured using the procedure of Nimmo and Perkins (2002), modified by Lehrsch et al (1991). The principal modification was that field-moist Ito 4-mm aggregates, rather than air-dry 1-to 2-mm aggregates, were aerosol-wetted using a non-heating vaporizer (Humidifier Model No 240, Hankscraft', Reedsburg, WI) prior to wet sieving.…”
Section: Laboratory Studymentioning
confidence: 99%
“…It was reported that the soil texture and its aggregates stability was affected by freezing and thawing process (Lehrsch et al 1991;Mbagwu and Bazzoffi 1989). Alternation of the soil freezing and thawing could effectively break the soil macro-aggregates into micro-aggregates and could increase the stability of soil aggregates on soil surface (Oztas and Fayetorbay 2003).…”
Section: Frozen Soil Layer Of Remediated Soilmentioning
confidence: 99%